Carnivoran remains from the Malapa hominin site, South Africa. - Kuhn, B.F.; Werdelin, L.; Hartstone-Rose, A.; Lacruz, R.S.; Berger, L.R. (Public Library of Science, 2011)
Recent discoveries at the new hominin-bearing deposits of Malapa, South Africa, have yielded a rich faunal assemblage associated with the newly described hominin taxon Australopithecus sediba. Dating of this deposit using U-Pb and palaeomagnetic methods has provided an age of 1.977 Ma, being one of the most accurately dated, time constrained deposits in the Plio-Pleistocene of southern Africa. To date, 81 carnivoran specimens have been identified at this site including members of the families Canidae, Viverridae, Herpestidae, Hyaenidae and Felidae. Of note is the presence of the extinct taxon Dinofelis cf. D. barlowi that may represent the last appearance date for this species. Extant large carnivores are represented by specimens of leopard (Panthera pardus) and brown hyaena (Parahyaena brunnea). Smaller carnivores are also represented, and include the genera Atilax and Genetta, as well as Vulpes cf. V. chama. Malapa may also represent the first appearance date for Felis nigripes (Black-footed cat). The geochronological age of Malapa and the associated hominin taxa and carnivoran remains provide a window of research into mammalian evolution during a relatively unknown period in South Africa and elsewhere. In particular, the fauna represented at Malapa has the potential to elucidate aspects of the evolution of Dinofelis and may help resolve competing hypotheses about faunal exchange between East and Southern Africa during the late Pliocene or early Pleistocene.
Keywords: accuracy; Acinonyx jubatus; article; Atilax; Canidae; Carnivora; Crocuta crocuta; dentition; Dinofelis; Dinofelis barlowi; Dinofelis piveteaui; Felidae; Felis margarita; Felis nigripes; Felis silvestris; fossil hominin; Genetta; genus; mandible; measurement; Megantereon cultridens; Megantereon whitei; morphology; nonhuman; Panthera pardus; Parahyaena brunnea; radiometric dating; South Africa; taxonomy; Vulpes; animal; Carnivora; classification; fossil; species difference